Nursing professionals perceptions on care at a birthing center - Greice Machado Pieszak; Marlene Gomes Terra; Eliane Tatsch Neves; Lizandra Flores Pimenta; Stela Maris de Mello Padoin; Lúcia Beatriz Ressel (Rev Rene)
The study aims at understanding how the nursing team perceives care during the birth process. It is a qualitative, descriptive and exploratory study carried out in the Birthing Center of a teaching hospital in southern Brazil. Data was collected through semi-structured interviews between August and September 2010 and then exposed to thematic contents analysis. Results suggest that the nursing team values practices that respond to the subjective needs of pregnant women based on human relations, emotions and good advice. It was concluded that the humanization of care is still a challenge for these professionals, however some improvements can be observed. It is recommended that nursing professionals invest in their role as facilitators of the care process in Birthing Centers, based on scientific knowledge aimed at a humanized care.